A Turning Point in the Translation of Shakespeare into Catalan: The Case of Josep M. De Sagarra’s Macbeth - Palomo Berjaga, Vanessa (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
Josep Maria de Sagarra translated twenty-eight of Shakespeare’s plays into Catalan in the early forties, at a time when Catalan language and culture were suffering severe repression due to Franco’s regime. The manuscript of Macbeth by Sagarra is from 1942; and the first edition (an impressive hard-bound clandestine edition) is from 1946 or 1947. Before his translation, there were three other Catalan translations of Macbeth, produced by Cebrià Montoliu (1907), Diego Ruiz (1908) and Cèsar August Jordana (1928). The main purpose of this article is to show that Sagarra’s translations marked a turning point regarding the translation of Shakespeare’s works in Catalan culture. This is done by reflecting on both cultural and personal circumstances that led Sagarra to translate Shakespeare and by comparing Sagarra’s translation of Macbeth with the other three from the first half of the twentieth century.